2017
DOI: 10.1007/s00338-017-1552-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term subaerial exposure on the cauliflower coral, Pocillopora damicornis, during a simulated extreme low-tide event

Abstract: Effect of short-term subaerial exposure on the cauliflower coral, Pocillopora damicornis, during a simulated extreme lowtide event. Coral Reefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 85 publications
1
10
0
1
Order By: Relevance
“…However, one colony from this site (G4) showed significantly higher levels of endosymbiont density following heat exposure. A similar response has been observed previously for Pocillopora colonies exposed to heat stress (see [38,54]). Indeed, corals are known to regulate their endosymbiont abundance upwards under sub-optimal conditions to sustain high photosynthetic yield [55].…”
Section: Discussionsupporting
confidence: 88%
“…However, one colony from this site (G4) showed significantly higher levels of endosymbiont density following heat exposure. A similar response has been observed previously for Pocillopora colonies exposed to heat stress (see [38,54]). Indeed, corals are known to regulate their endosymbiont abundance upwards under sub-optimal conditions to sustain high photosynthetic yield [55].…”
Section: Discussionsupporting
confidence: 88%
“…Lipids, proteins, and carbohydrates are the main energy substances of reef building corals, and they readily reflect changes in coral health (Yellowlees et al, 2008;Lesser, 2013). The synthesized carbon surplus from biological functions is the main energy source for calcification and reproduction (Castrillón-Cifuentes et al, 2017). According to our energy survey, the four identified coral species all had significantly lower protein content in the north compared with in the south, showing an adjusted energy structure.…”
Section: Energy Balance and Budgetmentioning
confidence: 88%
“…Grottoli et al (2014) and Schoepf et al (2015) showed that Porites astreoides keeps a high level of energy reserve in response to long-term bleaching stress, which is essential for a rapid recovery. Besides, during stressful periods, trade-off is made to maintain crucial functions by compromising obvious scope to growth (Zamer and Shick, 1987;Grottoli et al, 2014) or aberrant fecundity (Patton et al, 1977;Castrillón-Cifuentes et al, 2017), and energy budget is balanced by subtraction (Edmunds and Davies, 1989). For G. fascicularis, although it maintains high heterotrophic ability, its energy reserve was notably lower in the north compared with in the south side of WZZ.…”
Section: Energy Balance and Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Gorgona Island is located within a marine protected area so that direct anthropogenic impacts are virtually absent, these reefs are negatively affected by recurring natural disturbances such as El Niño warming events and subaerial exposures during extreme low tides (Zapata and Vargas-Ángel, 2003;Castrillón et al, 2017;Castrillón et al, 2017;Fiedler y Lavín, 2017). Por ejemplo, la cobertura de coral vivo en el arrecife de La Azufrada disminuyó en promedio 26% durante la década 1998-2008, siendo aún más crítico en las áreas someras del arrecife donde pasó de 61% a 15% (Zapata, 2017), a partir de donde ha ido recuperándose lentamente.…”
Section: Introductionunclassified